From grief to growth: The role of coping strategies, kinship and cause of death - Pereira, Marta (2024)
Background: Research has predominantly focused on the post-traumatic consequences of grief. Less is known about the factors associated with the capacity for recovery and growth. Objective: The main goal of this study is to analyse the mediating role of coping strategies in the relationship between the impact of the event and posttraumatic growth, considering the degree of kinship and the cause of death. Methods: This exploratory and correlational study, which used a cross-sectional design, involved a community sample of 889 adults who had lost a loved one. Results: Emotion and problem-focused coping strategies mediate the relationship between the impact of loss and posttraumatic growth, specifically when a spouse or a child dies. Conclusions: Individuals who experience greater suffering also undergo higher levels of post-traumatic growth. Coping strategies are crucial in post-trauma reconstruction and growth. Furthermore, the degree of kinship and the cause of death are decisive factors.